CODIFICATION AND TEXTBOOK PROJECT (International Library of African Music, 1969)
A primer of practical suggestions for field research for the Codification and Textbook Project has recently been published by the Library. It was written and compiled by Dr. Hugh Tracey, Andrew Tracey and Gerhard Kubik. The primer in itself, makes interesting reading for those who are in any way concerned with African Music.
Keywords: African Music